(untitled) (FAVE Sección Ciencias Agrarias, 2024)
Xanthomonas arboricola pv. juglandis is the bacterium responsible for the main walnut disease. The susceptibility of bacteriosis in the Chandler and Franquette cultivars was evaluated in two situations: with and without chemical treatments in the Valle Inferior de Río Negro. In the 2016/17 season, no preventive treatments were applied, in the 2017/18 season, 5 applications were made with copper products and mancozeb. The incidence and severity of the disease in leaves and fruits was registered in both seasons in the month of March. The two cultivars presented similar percentages (80 %) 0f incidence of the disease on leaves in the first season (2016/17); in the second season (2017/18), the incidence was lower in Franquette, differentiating it from Chandler (p = 0.0089). In both seasons, Franquette had a lower incidence of the disease in fruits (2016/17: p = 0.0161 and 2017/18: p = 0.0415). la severity of the disease on leaves, regardless of preventive applications, was greater in Chandler (2016/17: p < 0.0001 y 2017/18: p = 0.0066). The severity of the disease in fruits was higher in Chandler in both seasons (2016/17: p = 0.0037 y 2017/18: p = 0.0015). The severity of fruits in both cultivars was lower in the second season. The incidence of the disease in the two cultivars was high, however, when the severity in both seasons is analyzed, the degree of affectation is different, presenting a lower advance of the pathogen in the leaves and in the fruits of cv. Franquette.